Oral yeast-based DNA vaccine confers effective protection from Aeromonas hydrophila infection on Carassius auratus. Issue 84 (January 2019) - Han, Baoquan; Xu, Kun; Liu, Zhongtian; Ge, Wei; Shao, Simin; Li, Pengcheng; Yan, Nana; Li, Xinyi; Zhang, Zhiying
Abstract: Our previous study has demonstrated that recombinant yeast can induce specific immune responses in Carassius auratus and may serve as a potential carrier for oral DNA vaccines in aquaculture. In this study, we further developed an effective yeast-based oral DNA vaccine against the bacteria Aeromonas hydrophila, which was expected to provide protection from the motile aeromonad septicemia (MAS). First, two candidate antigen genes, ompG and omp48, were cloned from the Aeromonas hydrophila genome DNA. Then, relative yeast-eukaryote shuttle vectors were constructed and their expression in eukaryotes was validated. Next, crucian carps were orally administered with ompG or omp48 recombinant yeast, and the expression of the genes in the intestinal mucosa was confirmed by immunohistochemistry (IHC). The specific immune responses were further detected by Western blot and enzyme-linked immunosorbent assay (ELISA). The ELISA results showed that the production of the OVA-specific antibody in the OVA-ompG group was significantly higher than that of the OVA-omp48 group, indicating that the OVA - ompG group elicited obviously stronger immune response than OVA-omp48 . Finally, the challenge experiment against Aeromonas hydrophila infection demonstrated decreased fish mortality rate after the oral administration of the OVA - ompG yeast vaccine. In conclusion, our work provided a framework for the further development of oral yeast-based fishery vaccines. Highlights: A practical oral yeast-based DNA vaccine, which offers effective protection from Aeromonas hydrophila infection on carps, was developed. In vivo antigen-specific immune responses in carsp were induced by the oral administration of recombinant yeast. A superior antigen candidate can be used for the development of oral DNA vaccine in aquaculture.